Assessment of the stressed-strained state of a reinforced transport pipe under the combined effect of ambient temperature and static loads - Kovalchuk, Vitalii; Rybak, Roman; Hnativ, Yuriy; Tkachenko, Valentyna; Onyshchenko, Artur; Kravets, Ivan; Hermaniuk, Yuliia; Babyak, Mykola; Hembara, Nataliya; Velhan, Ihor (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is a reinforced three-layer transport pipe, which is subjected to the joint action of ambient temperature and static loading of the road subgrade soil. The analytical model for assessing the stressed-strained state of reinforced three-layer pipes, under the combined action of temperature and static loads, has been improved using the theory of elasticity. The stressed-strained state of the reinforced pipe was assessed taking into account the values of the joint action of temperature and loads from vehicles, the physical and mechanical parameters of structural materials, and the geometric parameters of the pipe. As a result of the calculation of the reinforced multilayer pipe, it was found that the maximum movements that occur on the outside of the defective pipe are 0.64 mm, the metal pipe – 0.75 mm, and in the concrete mortar (fine-grained concrete) – 0.69 mm. It was established that under the combined action of ambient temperature and static loads from the road subgrade soil, ring stresses are maximum. They are 151 MPa. Axial stresses are also high – 141 MPa. At the same time, the maximum radial stresses are the smallest – 37.4 MPa. It has been established that a small difference in displacements occurs on the contact of structural materials of the reinforced pipe. However, the magnitude of the stresses is high. The maximum difference in ring stresses was 73 MPa, while the difference in radial and axial stresses was up to 1.0 MPa. It has been established that to restore the bearing capacity of damaged reinforced concrete pipes, it is possible to use the repair technology by the method of "sleeving". It involves pulling a metal pipe into the middle of the layer damaged with concrete mortar remaining between the concrete defective and the new metal pipes.